Makna Tradisi Beseprah Erau Kutai Melalui Interaksi Simbolis dan Konstruksi Realitas Ritual - Saepullah; Al Mukarromah; Hanifah Jawahir (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2026)
This study aims to analyse the formation of shared meaning in the beseprah ritual within the Erau tradition of Kutai Kartanegara by applying the perspective of ritual communication theory, particularly through symbolic interaction and the construction of social reality. The research employs a qualitative approach with an interpretive case study design, using purposive and snowball sampling techniques to involve religious leaders, government officials, community figures, tourism ambassadors, and residents engaged in both the preparation and implementation of beseprah. Data were collected through in-depth interviews, participant observation, and documentation, then analysed thematically through stages of transcription, coding, categorization, and interpretation focused on ritual symbols, interaction patterns, and participants’ experiences of meaning.The findings reveal that beseprah creates shared meaning about togetherness and equality through the spatial arrangement of face-to-face seating, the use of white cloth as a food mat, collective prayers, the gong struck by the Sultan, and the practice of communal dining without social status barriers. These symbolic interactions construct a social reality of closeness between leaders and the people, a collective identity as a harmonious and cooperative community, and the preservation of local culture, which today is also mediated through social media.The study concludes that the beseprah ritual functions as a space of ritual communication that sustains identity, social solidarity, and the imagination of an egalitarian society, while simultaneously enriching the study of ritual communication and Islamic communication rooted in local wisdom.